A General Entry to Antifeedant Sesterterpenoids: Total Synthesis of (+)‐Norleucosceptroid A, (−)‐Norleucosceptroid B, and (−)‐Leucosceptroid K1. (4th September 2014) - Hugelshofer, Cedric L.; Magauer, Thomas
Abstract The first asymmetric total synthesis of the antifeedant terpenoids (+)‐norleucosceptroid A, (−)‐norleucosceptroid B, and (−)‐leucosceptroid K has been accomplished. This highly concise synthetic route was guided by our efforts to develop a platform for the collective synthesis of a whole family of antifeedant natural products. The synthesis features a Hauser–Kraus‐type annulation followed by an unprecedented, highly efficient intramolecular dilactol aldol‐type condensation reaction to produce the 5, 6, 5 skeleton. The developed synthetic route proceeds for norleucosceptroid A and B in 16 steps (longest linear sequence) from known compounds.